POTENTIAL ACCELERATING EFFECT OF Ageratum conyzoides L. LEAVES EXTRACT ON FIBROBLASTS DENSITY OF INCISION WOUND OF MALE WHITE MICE (Mus musculus) - Lestari, Mega Ayu; Sari, Ariestya Indah Permata; Amanah, Amanah (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Wound treatment using traditional medicine has been known widely in various countries in the world. Ageratum conyzoidesL. is commonly known by the ancient people to treat wound due to its potential anti-inflammatory effect. This study aims determine the effect of Ageratum conyzoidesL. leaves extract on fibroblast density of incision wound of male white mice (Mus musculus). Methods: This post-test only control group design experimental study used 35 male white mice which were randomly divided into five groups, i.e. negative control group K(-), positive control group K(+) (10% povidone iodine), and treatment group P1, P2, and P3 that were each given billy-goat weed leaf with increasing dose (15%, 30%, and 45% respectively). On each day, the length of the incision was measured by a ruler. After 7 days, the mice were terminated to obtain wound tissue which were used to prepare H&E stained histopathological sections to observe fibroblast density. Non-parametric analyses using Kruskall-Wallis and Mann Whitney test were used to compare the wound length and fibroblasts density. Results: Lengths of incision wound between all pairs of groups at the 7th day are significantly different (p< 0.05) with group P3 showed the shortest one. Significant differences were also observed in fibroblasts density between group K(-) and K(+), K(-) and P1, K(-) and P2, K(-) and P3, K(+) and P3, P1 and P3, P2 and P3 (p< 0.05) with group P3 showed the highest density among all groups. Conclusions: Ageratum conyzoidesL. leaves extract 45% has more potential effect than povidone iodine 10% in accelerating healing process by enhancing fibroblasts density.Â